2012
DOI: 10.1186/bcr3134
|View full text |Cite
|
Sign up to set email alerts
|

Protein tyrosine phosphatase Meg2 dephosphorylates signal transducer and activator of transcription 3 and suppresses tumor growth in breast cancer

Abstract: IntroductionSignal transducer and activator of transcription 3 (STAT3) is over-activated or phosphorylated in breast cancers. The hyper-phosphorylation of STAT3 was attributed to either up-regulated phosphorylation by several tyrosine-kinases or down-regulated activity of phosphatases. Although several factors have been identified to phosphorylate STAT3, it remains unclear how STAT3 is dephosphorylated by PTPMeg2. The aim of this study was to determine the role of PTPMeg2 as a phosphatase in regulation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 34 publications
3
76
0
1
Order By: Relevance
“…S4C. However, STAT5 phosphorylation was unchanged in this condition, which is consistent with our previous observation that PTPN9 interacts very weakly with STAT5 (Su et al, 2012). Another study showed that PTPN9 preferentially associates with JAK1 but not TYK2 and JAK2 (Hao et al, 2012).…”
Section: Dephosphorylation Of Stat3 By Ptpn9 Contributes To Erythroidsupporting
confidence: 81%
See 3 more Smart Citations
“…S4C. However, STAT5 phosphorylation was unchanged in this condition, which is consistent with our previous observation that PTPN9 interacts very weakly with STAT5 (Su et al, 2012). Another study showed that PTPN9 preferentially associates with JAK1 but not TYK2 and JAK2 (Hao et al, 2012).…”
Section: Dephosphorylation Of Stat3 By Ptpn9 Contributes To Erythroidsupporting
confidence: 81%
“…Our previous work has shown that PTPN9 directly dephosphorylates STAT3 in breast cancer cells (Su et al, 2012). Because STAT3 plays an important role in mammalian hematopoiesis, we hypothesized that Ptpn9a might also dephosphorylate Stat3 during zebrafish hematopoiesis.…”
Section: Ptpn9 Is Required For Erythroid Cell Maturationmentioning
confidence: 99%
See 2 more Smart Citations
“…Genetically silencing PTPN12 induces transformation and disrupts acinar formation in mammary epithelial cells (236). Levels of cytoplasmic protein tyrosine phosphatase non-receptor type 9 (PTPN9) inversely correlate with STAT3 in BC tissue (237). PTPN9 has been reported to inactivate STAT3 following EGFR dephosphorylation in breast cancer cells (238), suggesting that PTPN9 may play a critical role in BC development.…”
Section: Breast Cancermentioning
confidence: 99%